New species and records of pollen and sap beetles for Iran (Coleoptera: Kateretidae, Nitidulidae) - Audisio, Paolo; Cline, Andrew R.; Lasoń, Andrzej; Jelínek, Josef; Sabatelli, Simone; Serri, Sayeh (Zootaxa, 2017)
During recent expeditions in North and Southwest Iran, 10 species of Kateretidae and Nitidulidae (Coleoptera) were found. One species of Kateretidae, Brachyleptus bicoloratus Reitter, 1896, and three nitidulid species, Afrogethes schilskyi (Reitter, 1897), Stachygethes khnzoriani (Kirejtshuk, 1979), and S. nigerrimus (Rosenhauer, 1856) are recorded for the first time for the Iranian fauna (the latter is also a new record for Asia). Thymogethes ahriman (Jelínek, 1981) is herein resurrected to species rank, and two species, Thymogethes kassites sp. nov. and T. khorasanicus sp. nov., are described as new. An updated key to the known Near East and Afghan species of the genus Thymogethes Audisio & Cline, 2009 is also provided. Available and recently collected biological and distributional data, as well as short taxonomic comments, are given for the discussed species.